Maternal Obesity Increases Risk for Adverse Maternal Outcome at RSUP Dr. Mohammad Hoesin Palembang - Syifa Alkaf; Optima Fitra Ilhami; Mutiara Budi Azhar; Nuswil Bernolian; Ardesy Melizah (Indonesian Journal of Obstetrics & Gynecology Science, 2020)
Objective: To find the relationship between level of obesity and adverse maternal outcomes in pregnant women Method: An observational analytic study with a cross sectional design with secondary data from medical record. Subjects were pregnant women who gave birth at RSUP Dr. Mohammad Hoesin Palembang in January 2015-December 2017. Samples were taken by purposive sampling technique. BMIs  were divided into 5 categories based on WHO criteria, normoweight, overweight, obese level I, II, and III. Underweight was excluded from the study.Result: Of 252 research subjects, 94 (37.3%) were subjects with normal BMI, 102 (40.5%) were overweight, 44 (17.5%) were obese level I, 6 (2.4%) were level II, and 6 (2.4%) were level III. The maternal outcome consisted of 135 cases (53.6%) of preeclampsia, 6 cases of gestational diabetes mellitus (2.4%), 41 cases of uterine inertia (16.3%), 56 cases of preterm labor (22.2%), assisted delivery 111 cases (44%), and healthcare associated infections (HAIs) 6 cases (2.4%). Further analysis showed that increased level of maternal obesity is related significantly with preeclampsia, gestational diabetes mellitus, uterine inertia, and assisted delivery.Conclusion: There are statistically significant association between obesity level and the incidence of preeclamsia, gestational diabetes, uterine inertia and assisted delivery.Obesitas Pada Wanita Hamil Meningkatkan Morbiditas Maternal Di RSUP Dr. Mohammad Hoesin PalembangAbstrakTujuan: Untuk menemukan hubungan antara tingkat obesitas dengan luaran maternal pada wanita hamil. Metode: Studi analitik observasional dengan desain potong lintang menggunakan data sekunder rekam medis. Subjek adalah wanita hamil yang melahirkan di RSUP Dr.Mohammad Hoesin Palembang pada Januari 2015 - Desember 2017. Sampel diambil secara purposive sampling. Indeks massa tubuh (IMT) dibagi menjadi 5 sesuai kriteria WHO, yaitu normal, berat badan lebih, obesitas level I, II, dan III. Berat badan kurang diekslusi dari penelitian. Hasil: Subjek penelitian dari 252 orang, 94 (37.3%) subjek dengan IMT normal, 102 (40.5%) subjek berat badan berlebih,  44 (17.5%) obesitas level I,  6 (2.4%) obesitas level II, dan 6 (2.4%) obesitas level III. Luaran  maternal terdiri dari 135 kasus (53.6%) of preeklampsia, 6 kasus diabetes mellitus gestasional,  41 kasus inertia uteri  (16.3%), 56 kasus persalinan preterm (22.2%), 111 kasus (44%) persalinan pervaginam berbantu, dan infeksi luka 6 kasus (2.4%).  Analisis menunjukkan adanya tingkatan obesitas maternal berkaitan secara signifikan dengan kejadian preeklampsia, diabetes mellitus gestasional, inertia uteri, dan persalinan pervaginam berbantu. Kesimpulan: Terdapat hubungan antara tingkat obesitas pada ibu hamil dengan preeklampsia, diabetes mellitus gestasional, dan persalinan pervaginam berbantu. Kata kunci: Indeks Massa Tubuh, Obesitas, Luaran Maternal, Morbiditas.